Development of a Transparent Vehicle Administration System Using Web-Based Information Architecture: Pengembangan Sistem Administrasi Kendaraan yang Transparan Menggunakan Arsitektur Informasi Berbasis Web - IDO JAYA GAINAL; Eryan Ahmad Firdaus (FKOM UNIKU, 2026)
The management of official vehicles has historically relied on fragmented manual processes leading to inefficiencies, data inaccuracy, lack of transparency, and weak governance oversight. To address these challenges, this study designed and implemented Sikendi (Sistem Informasi Kendaraan Dinas), a web-based vehicle information system aimed at enhancing transparency and administrative governance. Using the System Development Life Cycle (SDLC) Waterfall approach, the system was developed with PHP, MySQL, JavaScript, and AJAX, featuring role-based access (Admin/User), integrated modules for vehicle registration, borrowing workflow with approval mechanisms, maintenance scheduling, fuel logging, document management, and activity auditing. Black-box testing confirmed functional compliance across 24 test cases for Admin and 15 for User roles. Results show the system significantly improves data accuracy, operational efficiency, and accountability, enabling real-time monitoring, automated reporting, and digital audit trails. This work demonstrates that digitizing fleet management in public sector institutions strengthens governance, reduces misuse risk, and supports data-driven decision-making, offering a replicable model for other governmental units